Video visitation in Australian prisons: perspectives on father-child contact - Hanley, Natalia (Trends & issues in crime and criminal justice, 2024)
Family visits for people in Australian correctional centres stopped during the COVID-19 pandemic. Video visitation was introduced in most jurisdictions as an alternative option. This paper presents the findings from the first multi-jurisdictional study to explore the experiences and impacts of video visits between fathers in prison and their children. Findings show that there are significant benefits to video visitation for fathers, children and children’s carers, and corrective services. However, video visits are most beneficial as a complement, not alternative, to contact visits. There are opportunities to develop support for fathers and carers by focusing on visit quality.